2023
DOI: 10.3390/epidemiologia4030026
|View full text |Cite
|
Sign up to set email alerts
|

Communicable Disease Surveillance in Lebanon during the Syrian Humanitarian Crisis, 2013–2019

Abstract: Lebanon has been one of the most affected countries by the Syrian humanitarian crisis. The national communicable disease surveillance was enhanced to detect outbreaks among Syrians. In this study, we aim to describe the findings of the communicable disease surveillance among Syrians in Lebanon, compare it to residents’ data, and describe the implemented surveillance activities between 2013 and 2019. During the study period, data on communicable diseases was mainly collected through the routine national surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A World Health Organization (WHO) assessment mission was conducted in 2016 to assess the national surveillance system in Lebanon, results showed compliance of 93%. 3 It is essential to keep active surveillance even in these difficult times to control this outbreak. Awareness should be created and invested in to target different audiences and inform them of the importance of vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A World Health Organization (WHO) assessment mission was conducted in 2016 to assess the national surveillance system in Lebanon, results showed compliance of 93%. 3 It is essential to keep active surveillance even in these difficult times to control this outbreak. Awareness should be created and invested in to target different audiences and inform them of the importance of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of vaccination among children is a major cause of the outbreak. 3 Socioeconomic factors play a major role in vaccination compliance, and contracting measles is itself associated with a significant economic burden. A recent study found several factors that hinder vaccination, including socio-demographics, knowledge, beliefs, and practices associated with age-appropriate vaccination.…”
Section: Immunizationmentioning
confidence: 99%
See 3 more Smart Citations